Physical activity and cardiometabolic health in adolescents with type 2 diabetes: a cross-sectional study. Issue 1 (14th May 2021) - Slaght, Jana L; Wicklow, Brandy Alexandra; Dart, Allison B; Sellers, Elizabeth A C; Gabbs, Melissa; Carino, Marylin; McGavock, Jonathan M
Abstract : Introduction: Youth living with type 2 diabetes display increased risk of cardiovascular disease (CVD). It is unclear if regular physical activity (PA) modifies this risk. Research design and methods: We compared CVD risk factors in a cross-sectional study of 164 youth with type 2 diabetes stratified according to weekly vigorous-intensity PA. Outcomes were hemoglobin A1c (HbA1c), ambulatory blood pressure (BP; ambulatory 24-hour readings), plasma lipoproteins, and albuminuria. The main exposure, vigorous-intensity PA, was quantified with the Adolescent Physical Activity Recall Questionnaire. Results: Youth were 15±3 years, and 78% lived rurally and 68% were female, with a mean body mass index (BMI) Z-score of 2.4±1.1 and a mean HbA1c of 9.6% ±2.6%. Youth who participated in regular vigorous-intensity PA (40%; n=67) achieved nearly twice the dose of PA than peers who did not (62 vs 34 metabolic equivalent score-hour/week, p=0.001). After adjusting for duration of diabetes, BMI Z-score, sex, and smoking, youth who engaged in vigorous-intensity PA displayed lower HbA1c (9.1% vs 9.9%, p=0.052), diastolic BP (70 mm Hg vs 73 mm Hg, p=0.002), diastolic load (20% vs 26%, p=0.023), and mean arterial pressure (87.3 mm Hg vs 90.3 mm Hg, p<0.01), compared with youth who did not. Compared with youth who did not participate in regular vigorous-intensity PA, those who did also displayed lower odds of albuminuria after adjusting for duration of diabetes, sex, smoking, rural residence, and BMI Z-score (adjusted OR: 0.40, 95% CI 0.19 to 0.84). Conclusions: Among youth with type 2 diabetes, participation in vigorous-intensity PA is associated with lower CVD risk.